Effect of inoculum and molasses concentration as supplement to vinasse of distillery for the production of biomass of native Candida utilis - Cajo, Lady (2013)
Vinasse is a residue of alcohol distilleries, rich in mineral salts and organic matter, whose use is limited and finally it is poured to the sewage system, causing pollution, nevertheless, can constitute a substrate for the production of biomass yeasts, used in the animal feed. In the present investigation was determined the effect of the concentration of the inoculum and the molasses as supplement of the vinasse, for the production of biomass of native Candida utilis. Yeasts were isolated of leaves of Zea mays L. "maize" in Sabouraud glucosade agar, were identified 40.23 % as C. utilis. Next, were cultivated in vinasse with 30 g/L of molasses, to 28 ºC, during 24 hours, the biomass was weighed and was selected C. utilis MKJ12, because it had the highest biomass value of 7.667 g/L. This yeast in concentration of 25, 50 and 75 mL/L of inoculum was cultivated in bioreactors Batch tank type containing 300 mL of vinasse with 10, 30, and 50 g/L of molasses, with downward air flow (1vvm), and incubation was 28 ºC during 20 hours. With 50 mL/L of inoculum and 50 g/L of molasses was determined the shortest generation time (2.88 h) and the highest values in number of generations (6.95), specific rate of growth (0.35 h-1), weight of biomass (11.78 g/L) and percentage of protein (40.15 %). Feasibility was demonstrated of the production of C. utilis biomass with 5 mL of inoculum in vinasse supplemented by molasses.